Impact Assessment of Fuel Subsidy Removal on Maize Value Added Products in Abia State Nigeria - Timothy, Christiana (European Science Publishing, 2024)
The study analysed Impact Assessment of Fuel subsidy Removal on Maize Value Added products in Abia State . A multi-stage random sampling technique was used in choosing the sample. Primary data collected from 120 maize value added entrepreneurs were used for the study. Data collected were analyzed using descriptive statistics. The result showed that the mean age of the entrepreneurs was 48years. Majority (58.34%) was female. The result of household size shows that the mean household size was 8 persons per household. The study further showed that 58.33% of the respondents were married. Majority (91.67%) of the respondents in the study acquired one form of formal education or the other. The entrepreneurs had processing experience mean of 14.86 years in maize value addition. About about 58.33% of the entrepreneurs in the area belong to cooperative society. The result from the distribution of Maize value added products showed that 25% of the respondents process their maize into Pap (akamu). About 16.67% of the respondent processed into pop corn, 17.5% processed into boiled corn, 13.33% processed into roasted corn, 12.5% processed into corn jellos (agidi), 8.33% processed into corn pudding (moi moi oka), 4.17% processed into animal feed, while about 2.5% processed into corn flour. The major constaraints to maize value addition includes capital, high cost of transportation, inflation rate, and high cost of inputs ranked top. The result on the cost of maize value added products before and after the removal of fuel subsidy showed that there is a 62% increase in the cost of 50kg bag of maize, 81% increase in price of 3.5kg of corn flour, 80% increase in price of 10kg of pap, 80% increase in price of 1kg of pop corn, 78% increase in price of 10 wraps of corn Jellos, 36.7% increase in the cost of animal feed (local chaff) 50% increase in the price of Labour. Important coping measures for entrepreneurs is to access agricultural loans so as to fully engage in the production of value added product of their choice, to buy a greater amount of maize grain, dry and keep in store as the prices of maize keeps increasing. And Processing a little quantity instead of being out of stock entirely.
Keywords: Maize, Fuel, Subsidy, Value Addition, Entrepreneurs, Agriculture, Farmers.